Pregnanolone Glutamate, a Novel Use-Dependent NMDA Receptor Inhibitor, Exerts Antidepressant-Like Properties in Animal Models - Holubova, Kristina; Nekovarova, Tereza; Pistovcakova, Jana; Sulcova, Alexandra; Stuchlík, Ales; Vales, Karel (Frontiers in Behavioral Neuroscience, 2014)
A number of studies demonstrated a rapid onset of an antidepressant effect of non-competitive NMDA receptor antagonists. Nonetheless, its therapeutic potential is rather limited, due to a high coincidence of negative side-effects. Therefore, the challenge seems to be in the development of NMDA receptor (NMDAR) antagonists displaying antidepressant properties, and at the same time maintaining regular physiological function of the NMDAR. Previous results demonstrated that naturally occurring neurosteroid 3α5β-pregnanolone sulfate shows pronounced inhibitory action by a use-dependent mechanism on the tonically active NMDAR. The aim of the present experiments is to find out whether the treatment with pregnanolone 3αC derivatives affects behavioral response to chronic and acute stress in an animal model of depression. Adult male mice were used throughout the study. Repeated social defeat and forced swimming tests were used as animal models of depression. The effect of the drugs on the locomotor/exploratory activity in the open-field test was also tested together with an effect on anxiety in the elevated plus maze. Results showed that pregnanolone glutamate (PG) did not induce hyperlocomotion, whereas both dizocilpine and ketamine significantly increased spontaneous locomotor activity in the open field. In the elevated plus maze PG displayed anxiolytic-like properties. In forced swimming PG prolonged time to the first floating. Acute treatment of PG disinhibited suppressed locomotor activity in the repeatedly defeated group-housed mice. Aggressive behavior of isolated mice was reduced after the chronic 30-day administration of PG. PG showed antidepressant-like and anxiolytic-like properties in the used tests, with minimal side-effects. Since PG combines GABAA receptor potentiation and use-dependent NMDAR inhibition, synthetic derivatives of neuroactive steroids present a promising strategy for the treatment of mood disorders.